Study On Feeding Practices Among Children 6 Months To 2 Years and Its Effect on Their Nutritional Status in Urban Slums - Katara, Parul S; Patel, Sangita V.; Kantharia, S L; Mazumdar, Vihang S; Shah, Malay B (National Journal of Community Medicine, 2013)
Background: The sheer rise in malnutrition in children during the first two years of life is indicative of poor feeding practices. Objectives: To study the Complementary Feeding (CF) practices in children of 6 months to 2 years of age and its effect on their nutritional status. Method: A sample size of 561 children between 6 months to 2 years was taken by cluster sampling method from urban slums. Results: Only 27% of children had started receiving CF at 6 months of age. Majority (82.5%) of children had feeding problem. Almost all (98.7%) children with moderate to severe wasting (WLZ) had feeding problem. Conclusions: Feeding problem was seen which was due to late initiation, incorrect quantity and type of CF given to the children. Malnutrition was seen more in children with feeding problem.